Non-cognitive predictors of undergraduates' attitudes to academic work in Nigerian Universities (2009)
This study investigated the relationship between non-cognitive variables, selection criteria scores, academic environment factors and attitudes of undergraduates to academic work. Six instruments were administered on 348 undergraduates composed of 191 males and 157 females from three universities in Nigeria. The study revealed that academic environment factors, study habits and use of academic materials were significant predictors of undergraduates' attitudes to learning various course works. These findings spell implication for counselling services for freshmen undergraduates, faculty administrators, lecturers and those in administrators, lectures and those in administrative capacities in tertiary institutions.